Laplace Transform With Modified Analytical Approximate Methods For Fractional Differential Equations - Jaber, Hailat Ibrahim Yousef (2022)
In this study, approximate analytical methods are highlighted. These methods are: the combination of the Laplace transformation with homotopy perturbation method (HPM) namely Laplace transform homotopy perturbation method (LT-HPM), Adomian decomposition method (ADM) namely Laplace transform Adomian decomposition method (LTADM), variational iteration method (VIM) namely Laplace transform variational iteration method (LT-VIM). The main target of this thesis is to improve and apply these methods to avoid the drawbacks and find the analytical approximate solutions for some cases of linear and nonlinear ordinary FDEs.